The Effect of Supplementation of Avocado Seed Flour (Persea americana Mill.) in Feed on Blood Lipids Profile and Egg Yolk Cholesterol of Japanese Quail (Corturnix-corturnix japonica) - Iriyanti, Ning; Tugiyanti, Elly; Apriyanto, Yosua Sujud (ANIMAL PRODUCTION, 2021)
The purpose of this research is to determine the effect of avocado seed flour (ASF) supplementation in feed on blood lipids and quail egg yolk cholesterol. The materials were 100 female quails aged 4 weeks old with ration ingredients consist of corn, bran, paddy, soybean meal, fish flour, avocado seed flour, palm oil, CaCO3, premix, lysine, and methionine. The research conducted an experiment with 4 treatments of ASF supplementation levels incorporated into basal feed, namely 0% ASF (R0), 3% ASF (R1), 6% ASF (R2), and 9% ASF (R3). The observed variables included blood cholesterol, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), triglyceride, and egg yolk cholesterol. The data were subjected to the one-way Analysis of variance (ANOVA) in a completely randomized design, followed by HSD test when differences between treatments were observed. The result showed that ASF supplementation significantly reduced blood cholesterol levels and the egg yolk cholesterol, did not significantly affect LDL and triglyceride levels. The HDL levels and egg yolk cholesterol tend to decrease as the level of ASF increased. It is concluded that avocado seed flour (ASF) supplementation up to 9% is safe for quail feed supplementation.